Evaluación biotoxicológica de Daphnias utilizando contaminantes provenientes de la actividad minera - Salvá Berenz, Miguel Ángel (2016)
The assessment evaluates aquatic ecosystems organisms known as Daphnia (water fleas), in the presence of pollutants that come from mining activity, by the applications of biotoxicological tests. The daphnias were chosen due to the fact, that they are very sensitive to contaminants and have an important role in aquatic ecosystems. They feed on smaller species and provide food for many fishes. The biotoxicological tests were applied in two particular cases, in both cases the Median Lethal Concentration (LC50) was obtained for daphnias in short tests (96 hours), using for this determination, the probit analysis curve. In the first case it was used a single pollutant (Copper solution 1000 ppm), where It was determined that the LC50 was 3.3 µg/L; in the second case there were used several contaminants (river as a receptor), and it was determined that the LC50 was 59%, It means that 59% is the river water and the 41% is distilled water.